Altered expression of maize PLASTOCHRON1 enhances biomass and seed yield by extending cell division duration - Sun, Xiaohuan; Cahill, James; Van Hautegem, Tom; Feys, Kim; Whipple, Clinton; Novák, Ondrej; Delbare, Sofie; Versteele, Charlot; Demuynck, Kirin; De Block, Jolien; Storme, Veronique; Claeys, Hannes; et al. (Nature communications, 2017)
Maize is the highest yielding cereal crop grown worldwide for grain or silage. Here, we show that modulating the expression of the maize PLASTOCHRON1 (ZmPLA1) gene, encoding a cytochrome P450 (CYP78A1), results in increased organ growth, seedling vigour, stover biomass and seed yield. The engineered trait is robust as it improves yield in an inbred as well as in a panel of hybrids, at several locations and over multiple seasons in the field. Transcriptome studies, hormone measurements and the expression of the auxin responsive DR5rev:mRFPer marker suggest that PLA1 may function through an increase in auxin. Detailed analysis of growth over time demonstrates that PLA1 stimulates the duration of leaf elongation by maintaining dividing cells in a proliferative, undifferentiated state for a longer period of time. The prolonged duration of growth also compensates for growth rate reduction caused by abiotic stresses.
Keywords: kyseliny indoloctové; Zea mays; Plant Leaves; Cell Division; semenáček; geneticky modifikované rostliny; kukuřice setá; regulace genové exprese u rostlin; listy rostlin; biomasa; Gene Expression Regulation, Plant; časové faktory; Gene Expression Regulation, Developmental; Cytochrome P-450 Enzyme System; Seeds; Plants, Genetically Modified; rostlinné proteiny; Seedlings; stanovení celkové genové exprese; Plant Proteins; Indoleacetic Acids; vývojová regulace genové exprese; Gene Expression Profiling; Biomass; Time Factors; systém (enzymů) cytochromů P-450; semena rostlinná; buněčné dělení